Tissue distribution of sodium p-perfluorous nonenoxybenzene sulfonate (OBS) in mice via oral exposure. (July 2022) - Zhou, Longfei; He, Sisi; Shi, Yali; Cai, Yaqi; Zhang, Chunhui
Graphical abstract: Highlights: OBS was detected in all 11 tissues and intestinal contents. The liver exhibited the highest OBS level, followed by the small intestine, lung, and kidney. Gender of mice will affect tissue distribution of OBS. Different distribution characteristics were observed for three isomers of OBS. Abstract: Environmental risks caused by emerging per- and polyfluoroalkyl substances (PFASs) have attracted increasing attention. As an important substitute for perfluorooctane sulfonate (PFOS), sodium p -perfluorous nonenoxybenzene sulfonate (OBS) is widely used as a firefighting foam additive and oil recovery agent in China. This study reported the tissue distribution of OBS in KM mice that were administered a dose of OBS at 10 µg/day via daily oral gavage for 7, 14, or 28 days. During exposure, gender-based differences were observed in body weight changes and tissue distribution of OBS. Liver exhibited the highest concentrations (males: 12.57 ± 1.80 µg/g; females: 11.80 ± 5.32 µg/g) and tissue/blood ratios and contributed more than 50% to the whole-body burden of OBS in both male and female mice, showing its ability to enrich PFASs. Furthermore, there were certain differences in the distribution characteristics of the three OBS isomers. Based on its bioaccumulation potential and widespread use, further studies are required on the human exposure risks of OBS.